2014
DOI: 10.1097/qai.0000000000000030
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Immune Reconstitution Inflammatory Syndrome in A5221 STRIDE

Abstract: Rationale and Objectives Earlier initiation of antiretroviral therapy (ART) in HIV-tuberculosis(TB) is associated with increased immune reconstitution inflammatory syndrome (IRIS). The severity, frequency and complications of TB IRIS were evaluated in A5221, a randomized trial of earlier ART (within 2 weeks after TB treatment initiation) vs. later ART (8-12 weeks after TB treatment) in HIV-infected patients starting TB treatment. Methods and Measurements In 806 participants, TB IRIS was defined using publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 17 publications
3
78
0
Order By: Relevance
“…3 The mortality of paradoxical TB-IRIS has been estimated as 3.2% within a recent meta-analysis, 13 and considerable rates of hospitalization and intervention in TB-IRIS patients have been observed. 23,24 Similar results were reported in a large randomized controlled trial (RCT) with the aim of optimizing the timing of HAART initiation. 25,26 Understanding the pathogenesis of PR and IRIS may improve clinical outcomes for these patients through promoting avoidance of PR/IRIS and identifying potential for immunotherapies, and may also contribute to a wider understanding of inflammatory pathologies in TB and mycobacterial diseases.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…3 The mortality of paradoxical TB-IRIS has been estimated as 3.2% within a recent meta-analysis, 13 and considerable rates of hospitalization and intervention in TB-IRIS patients have been observed. 23,24 Similar results were reported in a large randomized controlled trial (RCT) with the aim of optimizing the timing of HAART initiation. 25,26 Understanding the pathogenesis of PR and IRIS may improve clinical outcomes for these patients through promoting avoidance of PR/IRIS and identifying potential for immunotherapies, and may also contribute to a wider understanding of inflammatory pathologies in TB and mycobacterial diseases.…”
Section: Introductionsupporting
confidence: 70%
“…In HIV-seronegative individuals, low baseline lymphocyte counts at the time of TB diagnosis are associated with an increased risk of developing PR, 2,8 whilst in HIV-seropositive individuals, low CD4+ T cell counts have been related to subsequent IRIS in a range of studies. 13,18,23,24,34 Advanced HIV disease has also been identified as a risk factor for IRIS, consequent on high pre-HAART HIV-1 viral loads. 34 Given that a relationship between active TB and lymphopenia has been reported, 42 and it is suggested that active TB is associated with a degree of immunodeficiency, 43 one could hypothesize that a baseline immunodeficient phenotype in both HIV seronegative and seropositive individuals is implicated in the development of both PR and IRIS.…”
Section: Responses To Treatment Risk Factors and Pathogenesismentioning
confidence: 99%
“…Initiating antiretroviral therapy (ART) early during tuberculosis treatment in patients with advanced human immunodeficiency virus (HIV)/tuberculosis is associated with improved survival [1,2]; however, this strategy also increases risk for worsening of tuberculosis symptoms in a condition known as paradoxical tuberculosis-associated immune reconstitution inflammatory syndrome (TB-IRIS) [3][4][5]. The incidence of TB-IRIS ranges between 8% and 54% [6,7], and associated morbidity can be significant [3][4][5].…”
mentioning
confidence: 99%
“…The incidence of TB-IRIS ranges between 8% and 54% [6,7], and associated morbidity can be significant [3][4][5]. With the World Health Organization advocating early ART during tuberculosis treatment in highly immunosuppressed HIV/tuberculosis-coinfected patients [8], the incidence of TB-IRIS will likely rise [4].…”
mentioning
confidence: 99%
“…We suggest that a 4-month treatment regimen is adequate for treatment of HIV-negative adult patients with AFB smear-and culture-negative pulmonary TB [38]. IRIS may include high fever, worsening respiratory symptoms, inflammation and increased size of involved lymph nodes, new lymphadenopathy, expanding central nervous system lesions, worsening of pulmonary parenchymal infiltrations, new or increasing pleural effusions, and development of intra-abdominal or retroperitoneal abscesses [39].…”
Section: Hiv Infectionmentioning
confidence: 99%